INVESTIGATING THE EFFECT OF COVID-19 ON HUMAN RESOURCE MANAGEMENT AND NON-FINANCIAL JOB SATISFACTION: EMPIRICAL EVIDENCE FROM THE RMG SECTOR OF BANGLADESH - Sharif, Md. Azmir; Rahman, Md. Atiqur; Mallik, Mita Rani (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
This study aims to assess the impact on Human Resource Management (HRM) practices of the Ready-made Garments Sector, evaluate major changes due to COVID-19 in HRM, and examine employees' non-financial job satisfaction during COVID-19. This study collected data from 100 randomly selected respondents from Ready-made Garments of Bangladesh to accomplish these objectives. The findings show that job satisfaction (non-financial) has positive significant (p